2008
DOI: 10.1099/mic.0.2008/021204-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of Corynebacterium glutamicum to oxidative stress induced by deletion of the transcriptional repressor McbR

Abstract: In the present work the metabolic response of Corynebacterium glutamicum to deletion of the global transcriptional regulator McbR, which controls, e.g. the expression of enzymes of Lmethionine and L-cysteine biosynthesis and sulfur assimilation, was studied. Several oxidative stress proteins were significantly upregulated among about 40 proteins in response to deletion of McbR. Linked to this oxidative stress, the mutant exhibited a 50 % reduced growth rate, a 30 % reduced glucose uptake rate and a 30 % reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 48 publications
(47 reference statements)
4
30
0
Order By: Relevance
“…DNA binding by McbR is modulated by the small molecule S-adenosylhomocysteine, a byproduct of methylation reactions (185). Deletion of mcbR causes numerous pleiotropic effects on additional aspects of growth and metabolism, indicating that McbR plays a central role in regulating numerous physiological processes in C. glutamicum (186).…”
Section: Tfrs and Amino Acid Metabolismmentioning
confidence: 99%
“…DNA binding by McbR is modulated by the small molecule S-adenosylhomocysteine, a byproduct of methylation reactions (185). Deletion of mcbR causes numerous pleiotropic effects on additional aspects of growth and metabolism, indicating that McbR plays a central role in regulating numerous physiological processes in C. glutamicum (186).…”
Section: Tfrs and Amino Acid Metabolismmentioning
confidence: 99%
“…Marine bacteria possess various antioxidant mechanisms to eliminate reactive oxygen species (ROS), the inducers of oxidative stress (58). Particularly, NADPH is an oxidative stress protectant that is required by many important antioxidant defense mechanisms (75) and is important for counteracting oxidative stress (61,76,77). A recent study revealed the importance of the ED pathway for oxidative stress protection in P. putida (59).…”
Section: Discussionmentioning
confidence: 99%
“…Although the lack of high-level NADPH specificity for the glucose 6-phosphate dehydrogenase (Table 1) does not exclude at least a partial formation of NADH with the ED pathway in the corresponding strains, the nonspecificity of the enzyme surely enables the organism to cope with dynamic fluctuations in NADP ϩ and NADPH availability (73,75). Especially under conditions of oxidative stress, cells exhibit a drastically disturbed redox equilibrium and the NADPH/NADP ϩ ratio is reduced almost 10-fold (75). One can expect that this strongly promotes NADPH formation by glucose 6-phosphate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments provide the next level of systems biology studies, the parallel investigation of C. glutamicum on levels of gene expression, proteins, metabolites, and fluxes providing important links between the different functional components of cellular physiology. First examples of such systems-oriented studies already reveal a great potential [76,119,176]. Such approaches are especially promising for the targeted multidimensional alteration of complex regulatory networks towards better tolerance of production strains to high temperature or salt levels, or extreme pH values [137], but also reveal a great potential for efficient design of novel bioprocesses.…”
Section: Global Strain Engineering Through Applied Systems Biologymentioning
confidence: 99%